Indonesian Pre-Service EFL Teachers’ Attitudes and Motivation Toward English Language Learning - Nur Khofifah Harahap; Rahmah Fithriani (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2023)
Students' attitude towards language has an impact on their learning of English as a foreigner language (EFL). The significance of this language attitude cannot be overstated and may serve as a decisive factor in achieving success, alongside the learning motivation. One's language attitude is influenced by a range of factors, such as educational factors, social factors, and learner personality characteristics, among others. The objective of this investigation is to examine the perspectives of EFL pre-service teachers regarding the English language and their impetus for acquiring proficiency in English. An online survey was conducted using a Likert scale questionnaire to gather data from 80 Indonesian university students (18 males and 62 females) majoring in English education. The collected data is subsequently subjected to both qualitative and quantitative descriptive analysis. The study's findings indicate that non-native Indonesian pre-service EFL teachers exhibit a favorable attitude towards the English language and its learning. This research has revealed that pre-service teachers exhibit a strong inclination towards instrumental motivation, indicating a positive level of motivation. This study anticipates that forthcoming advancements can enhance the process of learning by aligning it with the pertinent methodology.